International Journal of Adolescent Medicine and Health (De Gruyter, 1985)
The International Journal of Adolescent Medicine and Health (IJAMH) provides an international and interdisciplinary forum for the dissemination of new information in the field of adolescence. IJAMH covers all aspects of adolescence. The International Editorial Board is dedicated to producing a high quality scientific journal of interest to researchers and practitioners from many disciplines.